2021
DOI: 10.1111/1759-7714.14042
|View full text |Cite
|
Sign up to set email alerts
|

Silencing LINC01116 suppresses the development of lung adenocarcinoma via the AKT signaling pathway

Abstract: Background: A growing body of evidence has proven that long noncoding ribonucleic acids (lncRNAs) are important epigenetic regulators that play crucial parts in the pathogenesis of human cancers. Previous studies have shown that long intergenic nonprotein coding RNA 01116 (LINC01116) is a carcinogen in several carcinomas; however, its function in lung adenocarcinoma (LUAD) has not been clarified. Here, we aimed to investigate the role of LINC01116 in LUAD. Methods: The relative expression levels of LINC01116 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…For instance, recent studies showed that a considerable number of patients with low expression of LINC01116 were generally diagnosed with TNM I rather than TNM I/III. These results indicate that LINC01116 can be considered as a latent regulator that participates in the progression of metastasis and invasiveness in LC ( Shang et al, 2021 ). Additionally, silencing of LINC01116 reverses this effect.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 76%
“…For instance, recent studies showed that a considerable number of patients with low expression of LINC01116 were generally diagnosed with TNM I rather than TNM I/III. These results indicate that LINC01116 can be considered as a latent regulator that participates in the progression of metastasis and invasiveness in LC ( Shang et al, 2021 ). Additionally, silencing of LINC01116 reverses this effect.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 76%
“…It has been shown that LINC00857 enhances BIRC5-dependent radio-sensitivity of cancer cells (Han et al, 2020), regulates apoptosis and glycolysis (Wang et al, 2020b), and is identified as one of the prognostic markers for the early stage lung adenocarcinoma (Mu et al, 2021). LINC01116 is oncogenic in several other kinds of tumors (Hu et al, 2018;Chen et al, 2020;Wu et al, 2020;Ye et al, 2020) and promotes lung adenocarcinoma proliferation and metastasis possibly via the Akt pathway (Zeng et al, 2020;Shang et al, 2021;Wu et al, 2021). The prognostic function of LINC00996 is also implicated in colorectal cancer (Ge et al, 2018), head and neck cancer (Ge et al, 2018), and multiple myeloma (Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 27 LINC01116 functioned as a competing endogenous RNA (ceRNA) to bind with miR‐744‐5p, regulate the downstream CDCA4 expression, and accelerate proliferation, migration, invasion, and cisplatin resistance of LUAD cell lines, 28 , 29 which could be blocked by the AKT signaling pathway. 30 LINC00324 acted as a ceRNA to interact with miR‐139‐5p and down‐regulated its expression, which accelerated the cell proliferation and invasion of NSCLC cell lines. 31 Pan et al 32 have also proved that LINC00324 promoted the proliferation and metastasis of LUAD tissues and cells by the miR‐615‐5p/AKT1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Up‐regulated LINC01137 enhanced the malignant tendency of oral squamous cell carcinoma cells and promoted the malignant transformation of oral cells 27 . LINC01116 functioned as a competing endogenous RNA (ceRNA) to bind with miR‐744‐5p, regulate the downstream CDCA4 expression, and accelerate proliferation, migration, invasion, and cisplatin resistance of LUAD cell lines, 28,29 which could be blocked by the AKT signaling pathway 30 . LINC00324 acted as a ceRNA to interact with miR‐139‐5p and down‐regulated its expression, which accelerated the cell proliferation and invasion of NSCLC cell lines 31 …”
Section: Discussionmentioning
confidence: 99%